Leveduras isoladas de pacientes com psoríase e indivíduos saudáveis: correlação clínica e sensibilidade de isolados de Malassezia Spp. E Candida Spp. A antifúngicos - Reis, Ane Teles (2020)
Psoriasis is a chronic inflammatory disease where several factors are related to the onset or worsening of the disease, including microorganisms such as yeasts of the genera Malassezia and Candida that are part of the human skin microbiota, but are associated with diseases such as pityriasis versicolor, dermatitis and candidiasis. Thus, the objective of the present study was to identify the yeasts present in lesions of patients with psoriasis and to compare with the skin of healthy individuals treated at the Hospital Universitário Walter Cantídio. Three study groups were considered: (I) Patients with the disease in activity without treatment; (II) Patients undergoing treatment for psoriasis; (III) Healthy individuals, without psoriasis. The patients' clinical-epidemiological data were evaluated. Up to five skin samples were collected in the three groups. The identifications of the isolated species were made by phenotypic, molecular characteristics (rDNA-RFLP) and MALDI-TOF MS. In vitro sensitivity tests for miconazole (MCZ), ketoconazole (KTZ), fluconazole (FLC), itraconazole (ITZ), voriconazole (VCZ), terbinafine (TRB) and amphotericin B (AMB) were performed using the Malassezia microdilution method. spp. and Candida spp., also biofilm formation of Malassezia spp in vitro. 61 people participated in the study, including patients and healthy individuals. Regarding patients with psoriasis, 60% were male (n = 21); patients in group I were younger (36.7 years ± 14.4) than those in group II (47.7 years ± 15.2). The most common clinical presentation was plaque psoriasis (85.71%), followed by pustular psoriasis (5.71%). In group I 57.2% of the patients had moderate to severe disease. In terms of treatment, 13 (50%) of patients in group II received phototherapy and / or topical treatment and the other 50% received systemic therapy. Malassezia, Candida, Rhodotorula and Trichosporon species were isolated in the three study groups. Candida spp. were isolated in 76.9% of the skin samples from healthy individuals. It was observed that the isolates of Malassezia spp. from patients had higher values of Minimum Inhibitory Concentration (MIC) for KTZ (0.29) and TRB (4.60), compared to those from healthy individuals. The Candida spp. from patients had higher MIC values for FLC (0.80) and lower for AMB (0.36) compared to those from healthy individuals. There was the formation of biofilms from Malassezia spp. in all tested isolates. The present study, despite sample limitations, brings important data for possible further investigations.